DESIGN OF EVACUATION EXITS IN ELLIPTICAL CORRIDOR TYPE BUILDINGS. CALCULATION ALGORITHM FOR WIDE CORRIDORS - Valery G. Shamonin; Alexey V. Golkin; Stanislav A. Zuev; Svetlana Yu. Khatuntseva; Petr A. Leonchuk (Актуальные вопросы пожарной безопасности)
The possibility of solving the problem of optimal choice of evacuation exits along one or both sides of curved corridors, both sides of which are parts of an ellipse, is considered for further minimizing the human flows mixing (and, accordingly, preventing congestion during movement of people) during evacuation in a fire or other emergency situations. An algorithm for determining the optimal distribution of outputs for wide corridors is presented.